Unpacking Best Applies: EFL Activator Teachers' Profiles and Practices on Critical Thinking Teaching - Silviya Izza Ulinnuha; Siti Muniroh; Suharyadi (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
The transformation of the latest Indonesian curriculum led to inevitable schemes, including the establishment of an activator teachers’ program. It is expected that teachers of better quality are produced in support of the aims of students' learning abilities, including critical thinking. Using qualitative and quantitative methods, this study is conducted to find the profiles and practices of EFL activator teachers. It involves 37 EFL activator teachers in East Java. While questionnaires are used to find the profiles of activator teachers, semi-structured interviews and observations are conducted to reveal how best EFL activator teachers implement critical thinking in the classroom. The findings show that activator teachers in general have a strong positive perception toward critical thinking in everyday classrooms; they also have medium practices of critical thinking teaching. Further investigation reveals that activator teachers do share a great amount of awareness in critical thinking. There are 4 strategies used by the teachers in prompting critical thinking; they are questioning, project/problem-based, group work, and the use of students’ feedback or reflection. The study implies the need for strengthened professional development to bridge the gap between teachers’ awareness and actual classroom practices in promoting critical thinking.